A Chemo-Genomic Approach Identifies Diverse Epigenetic Therapeutic Vulnerabilities in MYCN-Amplified Neuroblastoma - Krstic, Aleksandar; Konietzny, Anja; Halasz, Melinda; Cain, Peter; Oppermann, Udo; Kolch, Walter; Duffy, David J. (Frontiers in Cell and Developmental Biology, 2021)
Although a rare disease, neuroblastoma accounts for the highest proportion of childhood cancer deaths. There is a lack of recurrent somatic mutations in neuroblastoma embryonal tumours, suggesting a possible role for epigenetic alterations in driving this cancer. While an increasing number of reports suggest an association of MYCN with epigenetic machinery, the mechanisms of these interactions are poorly understood in the neuroblastoma setting. Utilising chemo-genomic approaches we revealed global MYCN-epigenetic interactions and identified numerous epigenetic proteins as MYCN targets. The epigenetic regulators HDAC2, CBX8 and CBP (CREBBP) were all MYCN target genes and also putative MYCN interactors. MYCN-related epigenetic genes included SMARCs, HDACs, SMYDs, BRDs and CREBBP. Expression levels of the majority of MYCN-related epigenetic genes showed predictive ability for neuroblastoma patient outcome. Furthermore, a compound library screen targeting epigenetic proteins revealed broad susceptibility of neuroblastoma cells to all classes of epigenetic regulators, belonging to families of bromodomains, HDACs, HATs, histone methyltransferases, DNA methyltransferases and lysin demethylases. Ninety-six percent of the compounds reduced MYCN-amplified neuroblastoma cell viability. We show that the C646 (CBP-bromodomain targeting compound) exhibits switch-like temporal and dose response behaviour and is effective at reducing neuroblastoma viability. Responsiveness correlates with MYCN expression, with MYCN-amplified cells being more susceptible to C646 treatment. Thus, exploiting the broad vulnerability of neuroblastoma cells to epigenetic targeting compounds represents an exciting strategy in neuroblastoma treatment, particularly for high-risk MYCN-amplified tumours.